2021
DOI: 10.1002/solr.202100010
|View full text |Cite
|
Sign up to set email alerts
|

A Coadditive Strategy for Blocking Ionic Mobility in Methylammonium‐Free Perovskite Solar Cells and High‐Stability Achievement

Abstract: Herein, the synthesis of methylammonium‐free and bromide‐free CsxFA1−xPbI3 (FA for formamidinium) perovskite (PVK) photovoltaic layers with intrinsic outstanding properties in terms of crystallinity, defect waiving/passivation, and ionic mobility blocking by using a coadditives approach is described. It consists in mixing two chloride additives in the PVK precursor solution: potassium chloride (KCl) and ammonium chloride (NH4Cl). KCl favors the lead iodide (PbI2) precursor solubilization and results in a purer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…Different components can bring desired properties, such as improved optical properties or structural stability. To achieve better performance of PSC, perovskite materials composition has been complexified by combining several A + monovalent elemental and organic cations, from double-cation (e.g., MA-FA, [13,14] Cs/FA, [15,16] Rb/FA, [17] MA + being methylammonium and FA + being formamidinium) to triple-cation (e.g., Cs/MA/ FA, [8,18,19] Rb/MA/FA, [20] K/Cs/FA [21] ), and quadruple-cation (Rb/Cs/MA/FA [18,22] ). The incorporation of other cations, namely MA + , Cs + , Rb + and K + , aims at alleviating the formation of photo inactive δ-FAPbI 3 phase and/or suppress defects in perovskite film.…”
mentioning
confidence: 99%
“…Different components can bring desired properties, such as improved optical properties or structural stability. To achieve better performance of PSC, perovskite materials composition has been complexified by combining several A + monovalent elemental and organic cations, from double-cation (e.g., MA-FA, [13,14] Cs/FA, [15,16] Rb/FA, [17] MA + being methylammonium and FA + being formamidinium) to triple-cation (e.g., Cs/MA/ FA, [8,18,19] Rb/MA/FA, [20] K/Cs/FA [21] ), and quadruple-cation (Rb/Cs/MA/FA [18,22] ). The incorporation of other cations, namely MA + , Cs + , Rb + and K + , aims at alleviating the formation of photo inactive δ-FAPbI 3 phase and/or suppress defects in perovskite film.…”
mentioning
confidence: 99%
“…In inorganic chloride additives, the cation includes alkali metal (K + , Na + , Li + ), [50] Pb 2+ , Mn 2+ , [44] and ammonia species NH 4 + [50] . Normally, inorganic chloride additives present in the PVK precursor solution increase the grain size as well as enhance the grain orientation and finally often increase the PCE of the device.…”
Section: Chloride Additives For Pvk Filmsmentioning
confidence: 99%
“…Zheng et al. have clearly shown that K + from KCl suppresses iodide mobility in PVK and linked it to J ‐ V curve hysteresis cancellation [50] …”
Section: Chloride Additives For Pvk Filmsmentioning
confidence: 99%
See 2 more Smart Citations